Comprehensive Midwifery Care Case Study in NY. N.I at Puskesmas Toto Utara, Bone Bolango - Magdalena M Tompunuh; Nur Inayah Adam (Poltekkes Kemenkes Gorontalo, 2021)
World Health Organization (WHO) stated that in 2017 the number of maternal deaths in the world was around 295,000, with the mortality of young mothers being around one in 190 people. The Maternal Mortality Rate (MMR) in Indonesia in ASEAN countries is in the second highest position after Laos, namely 305 per 100,000 live births. In order to reduce the impact of these deaths, the government seeks to create programs with comprehensive services that include the provision of integrated services for mothers and babies from pregnancy to delivery, newborns and the post-natal period. In addition, one of the efforts to reduce MMR and IMR and also produce quality health services is to provide comprehensive care for pregnancy, childbirth, newborns and childbirth. The purpose of this case study is to provide comprehensive midwifery services to mothers from pregnancy to childbirth using a 7-step Varney approach and documentation through SOAP. Case Study Method with Case Study at North Toto Health Center, Bone Bolango District, at Mrs. NI, aged 22 years, from December 2019 to February 2020, using primary and secondary data, data collection techniques from interviews, observation, examination and documentation studies, data analysis in accordance with midwifery management. Case Report and Discussion The results of this case study obtained a diagnosis of G1P0A0 gestational age 37-38 weeks physiologically with physiological delivery, physiological puerperium, and physiological newborn babies.